Physiological potential and fungi control of Moringa oleifera Lamark seeds treated with essential oils - Medeiros, Maria Luiza de Souza; de Jesus, Hanna Ibiapina; de Farias, Otília Ricardo; Cruz, José Manoel Ferreira de Lima; do Nascimento, Luciana Cordeiro (Scientia Plena, 2020)
Moringa oleifera Lam. is a fast-growing, drought-resistant, rustic plant with high nutritive value. The aim of the present study was to determine the effectiveness of essential oils from citronella grass (Cymbopogon winterianus), lemongrass (Cymbopogon citratus) and thyme (Thymus vulgaris) on the reduction of the incidence of fungi associated with moringa seeds as well as the influence of these oils on the physiological quality of the seeds. Two experiments were conducted, both with an entirely randomized design. The seeds were treated with the citronella, lemongrass and thyme essential oils at concentrations of 250 and 500 µL (100 seeds per treatment). The fungicide Captan was used as the control treatment. The incidence of fungi on the treated seeds was evaluated in the first experiment. The germination percentage, shoot length, primary root length, shoot dry mass and root dry mass of the seedlings were evaluated in the second experiment. The most incident fungus was also isolated for the transmission test. The following fungi were identified on the moringa seeds: Fusarium spp., Nigrospora sp., Aspergillus sp., Penicillium sp., Alternaria sp., Phomopsis sp., Curvularia sp., Colletotrichum sp., Pestalotipsis sp., Lasiodiplodia sp. and Chaetomium sp. The essential oils significantly reduced the incidence of the fungi. However, changes in the physiological quality of the seeds were associated with the use of the oils. No transmission of Fusarium spp. from the seeds to the seedlings occurred, but this fungus caused the rotting of seeds in the germination phase.